2013
DOI: 10.5114/ceji.2013.37753
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the effect of the buckwheat protein hydrolysate on bacterial adhesion, physiology and cytokine secretion of Caco-2 cells

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The construction of the standard curve for each real-time PCR analysis was based on bacterial strains from our own culture collection and from the German Collection of Microorganisms and Cell Cultures. Each bacterial culture was separately cultivated in appropriate conditions (details available upon request), and the cell count was determined using 4′,6-diamidino-phenylindole (Sigma-Aldrich) with a procedure described elsewhere [21]. Two millilitres of each culture was centrifuged (5 min, 10,000× g ), washed with sterile PBS (pH 7.4) and then centrifuged again.…”
Section: Methodsmentioning
confidence: 99%
“…The construction of the standard curve for each real-time PCR analysis was based on bacterial strains from our own culture collection and from the German Collection of Microorganisms and Cell Cultures. Each bacterial culture was separately cultivated in appropriate conditions (details available upon request), and the cell count was determined using 4′,6-diamidino-phenylindole (Sigma-Aldrich) with a procedure described elsewhere [21]. Two millilitres of each culture was centrifuged (5 min, 10,000× g ), washed with sterile PBS (pH 7.4) and then centrifuged again.…”
Section: Methodsmentioning
confidence: 99%
“…While rutin was the most abundant flavonoid measured, it did not show significant cytotoxicity. The studies of Ishii et al [ 29 ], and Swiatecka et al [ 36 ], used colon cancer lines to test buckwheat-derived products but showed conflicting results. Ishii et al [ 29 ] compared the LPS-induced response from human carcinoma cell lines (CoLoTC) and extracts from buckwheat.…”
Section: Resultsmentioning
confidence: 99%
“…They used IL8 as a biomarker for inflammation and found that the buckwheat extracts significantly lowered IL8 expression in colon cancer cells in a dose-dependent manner but did not influence cell viability. On the other hand, Swiatecka et al [ 36 ] tested buckwheat protein hydrolysate on the CaCo-2 cell line, resulting in significantly lower cell proliferation and significantly higher levels of IL8. In another study, Kim et al [ 37 ] prepared extracts from buckwheat hull with multiple fractions of different solvents (ethanol, ethyl acetate, hexane, butanol, chloroform, and water) and tested them to multiple cancer lines (human gastric carcinoma, human hepatocellular, carcinoma, human lung carcinoma, human breast adenocarcinoma, and human cervical adenocarcinoma).…”
Section: Resultsmentioning
confidence: 99%
“…The IL-8 production by intestinal cells in response to bacterial stimuli depends on the specific epitopes present on bacterial surface, such as pathogen-associated molecular patterns (PAMPs) being ligands for TLRs. Activation of different TLRs by complex microbial consortia activates the innate immune response, and the final direction of immune response (pro- or anti-inflammatory) depends on the specific composition of the microbial consortium [ 36 , 37 , 38 , 39 ]. In our study, there was no significant difference in IL-8 secretion when compared healthy and cancer colonocytes treated only with V or O bacteria ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%